Stress-strain behavior and shear strength of unsaturated residual soil from triaxial tests - Leong, Eng Choon (2013)
Multi-stage triaxial compression tests were performed on undisturbed samples of residual soils from Bukit Timah Granite formation in Singapore. Tests were carried out under two conditions, namely, consolidated undrained test (CU) (i.e. both pore-air and pore-water pressure were not allowed to drain during shearing) and constant water content test (CW) (i.e. drained pore-air but undrained pore-water condition during shearing). Stress-strain relationships and shear strength of unsaturated soils were studied at different initial matric suctions of 50 kPa, 100 kPa, 200 kPa, and 400 kPa, by performing CU and CW tests. The variations of matric suction during shearing at two different test conditions (CU and CW tests) are also presented. From the experiments, it was observed that the stress-strain relationship from CU test is less stiff than that from CW test. A single relationship of total cohesion intercept with matric suction was obtained from CU and CW tests.